QIRÂAH FÎ KHIȚÂB AL-MAR’AH: STUDI ISU GENDER DALAM KITAB DAWÂIR AL-KHAWF - Daud, Fathonah K.; Hambali, HM Ridlwan (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2024)
This article examines gender issues in the thoughts of Naṣr Ḥāmid Abu Zayd as stated in his book entitled Dawâir Al-Khawf Qirâah Fî Khițâb Al-Mar'ah. Naṣr Ḥāmid was originally a follower of Al-Ikhwan al-Muslimun, who later turned into a liberal intellectual figure from Egypt who was known for his controversial and controversial thoughts. This study uses a literature study which refers to several main books of his works and is added to secondary sources in the form of several writings resulting from research on the thoughts of Naṣr Ḥāmid Abu Zayd. The results of this research show that Naṣr Ḥāmid criticizes the interpretations that have developed over time, especially regarding qiwâmah, inheritance, talak, polygyny and women's private parts (hijab). According to him, women are part of the substance that is rooted in human social existence in certain historical realities. These conditions of social relations determine the position of men and women equally in the social, cultural and intellectual framework. Both are equal as complete human beings. This thinking places him at the level of progressive thought and attracts many groups, which is sometimes in harmony with the ideas of early Egyptian Muslim feminists, namely Muhammad Abduh.